2019
DOI: 10.1177/1938640019826699
|View full text |Cite
|
Sign up to set email alerts
|

Syndesmotic Fixation With Suture Button: Neurovascular Structures at Risk: A Cadaver Study

Abstract: Objectives: The objective of this study was to describe the anatomic variations in the saphenous nerve and risk of direct injury to the saphenous nerve and greater saphenous vein during syndesmotic suture button fixation. Methods: Under fluoroscopic guidance, syndesmotic suture buttons were placed from lateral to medial at 1, 2, and 3 cm above the tibial plafond on 10 below-knee cadaver leg specimens. The distance and position of each button from the greater saphenous vein and saphenous nerve were evaluated. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…10 Hence, routine medial incision to prevent iatrogenic injury to the medial neurovascular structures and accurate positioning of the medial suture button has been recommended. 2,6,[8][9][10] The complications associated with the medial suture button are not new and the introduction of new suture button deployment devices aimed to reduce risk to medial neurovascular structures and soft tissue while providing accurate implant positioning and reducing the need for a medial incision. 1 A recent cadaveric study had investigated this type of device on 10 specimens with 40 suture buttons at the respective 1.0-to 4.0-cm zone above the ankle mortise using fluoroscopic guidance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…10 Hence, routine medial incision to prevent iatrogenic injury to the medial neurovascular structures and accurate positioning of the medial suture button has been recommended. 2,6,[8][9][10] The complications associated with the medial suture button are not new and the introduction of new suture button deployment devices aimed to reduce risk to medial neurovascular structures and soft tissue while providing accurate implant positioning and reducing the need for a medial incision. 1 A recent cadaveric study had investigated this type of device on 10 specimens with 40 suture buttons at the respective 1.0-to 4.0-cm zone above the ankle mortise using fluoroscopic guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Syndesmosis injuries have been treated with suture button fixation devices with rising popularity over the last 15 years. [2][3][4][5][6][7][8][9]11 Although there is no consensus on the optimal fixation device for syndesmosis injury, 3 multiple studies have reported advantages such as the dynamicity of fixation to allow anatomical movement of the joint while keeping reduction, obviation of screw breakage, elimination of implant removal, and reduction in risk of late diastasis with the use of the suture button device. 2,3,[6][7][8][9]11 Despite the reported superiority over conventional screw fixation, 3,4,7,11 reports of complications such as stitch granuloma and formation of abscess due to the prominent suture knot, construct loosening, osteomyelitis of the distal tibia, and pathologic fracture through the drill hole have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations